(untitled) (Scripta Theologica, 2018)
The author’s intention is to draw attention to the biblical morality and personalism of Vatican II. Granted that there are other valid criteria on which to base the objectivity in morality, he wishes to highlight the importance of the dignity of the human person and council’s reference to Christ as the fundamental criteria in the teaching of Vatican II. Objectivity, immutability, and transcendence rest on Christ, the centre of history, and on the dignity of the human person. He points out that other valid perspectives are possible but Vatican II opted for this for several reasons. The reference to Christ expresses the necessary recourse to God and is in the line of the scholastic formula: a Deo, ad Deum, secundum Deum. Revelation brings with it mysteries, truths and norms which claim a response of faith and love, a homage of the intelligence and will that is in keeping with session VI of Trent. The Second Vatican Council considers historic nature in a unique divine vocation. It reaffirms the gratuity of the supernatural but does not use the hypothesis of natura pura. Recourse to the dignity of the human person allows the Council to address itself to all men, since this dignity is based on creation and on the one vocation to salvation. The centre of this dignity is the moral conscience which should act respecting the objective norms of morality. The ideal presented by the Council asks for a moral effort parting from the data provided by faith and from a personalist philosophy. It is not true that personalism necessarily leads to subjectivism. The council has shown it. The person is an objective reality and the path from personalism to the transcendence is consistent with the lines of the fourth way of St Thomas: the participated transcendence of the person is based on the absolute transcendence of God. The Church dialogues with the world conscious that in Christ it possesses the full truth about man, about all men since all are called to salvation. This is what makes it possible for the Church to cooperate with the world, to discover the positive side of progress and at the same time it allows and obliges both the Church and christians to have a critical function. Although granting that christians and non-christians should consider themselves invited to cooperate in common action, it is necessary to note the existence of serious conflicts, ever more frequent in a pluralist society. Human progress is not the same as the Kingdom of God. Sometimes one opposes the other and on this account the christian should adopt a critical attitude with respect to attempted developments contrary to human dignity in view of his commitment to the faith and to the dignity of the human person.